1986
DOI: 10.3177/jnsv.32.111
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chronic intake of new sweetener fructooligosaccharide (Neosugar) on growth and gastrointestinal function of the rat.

Abstract: SummaryThe influence of the chronic intake of a newly developed sweetener named "Neosugar" (fructooligosaccharide) on body weight gain, organ weight, serum lipids, fecal excretion and intestinal function was investigated in rats. The following results were obtained. 1) Body weight gain was diminished more severely in rats fed on 20% Neosugar diet than in rats fed on 10% Neosugar diet. 2) The wet weights of cecum and colon were greatly increased by Neosugar feeding. 3) Fecal wet weight was significantly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
67
5
4

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(84 citation statements)
references
References 21 publications
(11 reference statements)
7
67
5
4
Order By: Relevance
“…FOS, which has a 1-2 b bond unit of two molecules of fructose, cannot be hydrolyzed in in vitro assay using small intestinal enzymes of rat. In addition, it has been demonstrated that orally ingested FOS escapes digestion in the small intestine and is metabolized to carbon dioxide via short-chain fatty acids produced by colonic microbes (Tokunaga et al, 1986(Tokunaga et al, , 1989. Breath hydrogen gas excretion of GS was lower than that of FOS.…”
Section: Discussionmentioning
confidence: 99%
“…FOS, which has a 1-2 b bond unit of two molecules of fructose, cannot be hydrolyzed in in vitro assay using small intestinal enzymes of rat. In addition, it has been demonstrated that orally ingested FOS escapes digestion in the small intestine and is metabolized to carbon dioxide via short-chain fatty acids produced by colonic microbes (Tokunaga et al, 1986(Tokunaga et al, , 1989. Breath hydrogen gas excretion of GS was lower than that of FOS.…”
Section: Discussionmentioning
confidence: 99%
“…these saccharides, increase during repeated ingestion (7,23). Tolerance of the ingestion of these sugar substitutes, expressed as the relation between dose levels and symptoms, shows considerable individual variation.…”
Section: Discussionmentioning
confidence: 99%
“…The non-effective dose level per kg of body weight in a single ingestion depends on the digestibility and absorbability of sugar substitutes such as sugar alcohols and oligosaccharides (5). It is also influenced by other factors such ingestion at multiple times in a day (24), the properties of the test substance, and acclimation to the test substance after repeated ingestion (7). For example, the maximal permissible dose increased about 1.5 times after one container of chocolate containing lactitol was repeatedly ingested every day by healthy female subjects for 10 d (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…These dietary components, such as inulin (16), resistant starch (38), and guar gum hydrolysate (9), increase apparent intestinal calcium absorption, calcium balance, and bone mineral density in rats. The stimulatory effects of fructooligosaccharides (FOS), which are low-molecular-weight indigestible carbohydrates (31,42), on intestinal calcium absorption have been particularly well examined (23,24,27). FOS also increases true and apparent intestinal calcium absorption, calcium balance, and bone mineral density in growing rats (22,23).…”
Section: Fos and Mineral Absorptionmentioning
confidence: 99%